Mental Health Determinants And Risk Behaviors of High School Students - Agustini, Rina Tri; Nurrachmawati, Annisa; Rohmah, Nur; Permana, Lies; Feriyanti, Alma; Rahayu, Agustin Putri; Fikri, Mohammad (Universitas Airlangga, 2026)
Background: According to the Basic Health Research Survey (Riskesdas), the prevalence of depression in the population aged 15–24 years is 6.2%. Adolescents are prone to a variety of risky behaviors, such as drug abuse, unsafe sexual behaviors, and unhealthy diets. Objective: The purpose of this study was to analyze risky behaviors related to mental health determinants in high school students. Methods: This cross-sectional study was conducted in North Balikpapan, Samboja, and Sepaku Districts, which serve as buffer zones of the National Capital, particularly at SMAN 9 Balikpapan (n=248), SMAN 2 Samboja (n=110), and SMAN 3 Penajam Paser Utara (n=28), during October–November 2024. The dependent variables measured were health risk behaviors, and the independent variables were determinants of mental health. A multivariate analysis was performed using a binary logistic regression test. Results: Family mental health status was found to increase the likelihood of smoking behavior by 2.282 times (p=0.005). Meanwhile, psychological pressure on students increased the likelihood of excessive time spent staring at a gadget screen by 2.126 times (p=0.018). Additionally, family mental health status had a protective effect against low physical activity in students (p=0.010, OR=0.198). Conclusion: Psychological distress and family mental health significantly influence adolescent risk behaviors. Further research is needed to explore the physiological aspects of stress and the impact of family mental health on risky behaviors in adolescents.